In Situ Study of Electropolymerized Poly(3-aminobenzoic acid) Thin Film on BD-R and DVD-R Grating Substrates by Electrochemical-Transmission Surface Plasmon Resonance Spectroscopy - Saengrawee Sriwichai; Akira Baba; Sukon Phanichphant; Kazunari Shinbo; Keizo Kato; Futao Kaneko (International Journal of Polymer Science)
The electropolymerization process and doping/dedoping properties of poly(3-aminobenzoic acid) (PABA) thin films on gold-coated commercial BD-R and DVD-R grating substrates were simultaneously studied by the combination of electrochemical technique and transmission surface plasmon resonance (TSPR) spectroscopy. The optical property as a function of the applied potentials and time dependence during electropolymerization were studied. The obtained TSPR wavelength scan spectra after electropolymerization showed that the maximum wavelength slightly shifted to longer wavelength indicating the increase of film thickness. In addition, the change during construction of PABA-based immunosensor for label-free detection of human immunoglobulin G can be observed.